760 IMPROVING THE MANAGEMENT AND DURATION OF RESOLUTION OF ACUTE KIDNEY INJURY IN THE ELDERLY. (8th March 2022) - Ghaddar, Y; Stevens, A; Pearl, M; Sivagnanam, T; Sheriff, S P
Abstract: Introduction: Acute Kidney Injury (AKI) is prevalent in elderly populations due to several factors: polypharmacy, anatomic/physiologic changes of the kidneys associated with aging. AKI can contribute to increased length of stay, morbidity and mortality. This audit sets out to establish if the guidance established by NICE is being followed and how it may be better implemented. Method: This study audited patients ≥65 years, who were admitted with AKI/developed an AKI during admission. Patients were excluded if they were on renal replacement therapy or under palliative care. Data was collected from case notes and Clinical Work Station. Data collection points used included: senior review within 24 hours; assessment of fluid status; medication review; strict fluid balance; examine for retention +/− catheter; daily U&E and appropriate imaging. Our independent variable was an AKI sticker, this included a revised checklist for above data collection points that was applied to patients' medical notes. In addition to this, we used posters on appropriate wards which explained the guidance and management of AKI. Awareness was continued by presenting at Care of The Elderly teaching and medical grand round. Then re-audited the following month. Results: Both cycles involved 45 patients. After implementation, improvements in urine analysis (5%vs35%), assessments of retention (0%vs38%) and assessments of fluid balance (55%vs78%) were seen. In cycle 2, medication was reviewed more frequently, specifically a 30% increase in the review of nephrotoxics. While senior review within 24 hours remains high in both cycles. We measured the outcome by checking the resolution time of AKI. Mean Resolution time was reduced by 1.4 days. Conclusion: This audit has demonstrated an increase in the optimisation of the management of AKI through ensuring all appropriate interventions and examinations are completed and reducing resolution time by using stickers and the posters.